Benefit maximisation based on aggregated condition indices: drawbacks for selection of pavement treatments. Issue 1 (2nd January 2022) - Donev, Valentin; Hoffmann, Markus; Blab, Ronald
ABSTRACT: Road agencies employ different criteria and methods to compare treatment alternatives and develop maintenance and rehabilitation (M&R) programmes for their networks. The maximisation of benefits has been integrated in several leading pavement management systems and used for network-level programming since the 1980s. The approach defines benefit as the area between the performance curves with and without M&R actions based on an aggregated index, representing the overall pavement condition. Further simplifications like the screening of solutions using an efficiency frontier and the incremental benefit–cost technique have made it possible to apply the method with the available computing power at the time. Based on a case study of 1000 road sections, this paper analyses the effect of benefit maximisation on annual budget, network condition, treatment selection, trigger values and remaining life. M&R programmes minimising costs and maximising benefits are compared at the project and network level for various budget scenarios. The results show that the maximisation of benefits based on an aggregated condition index leads to substantially higher agency costs and favours the selection of expensive treatments with earlier timing, irrespective of actual failure causes. The conclusions of this work may be useful to road agencies in developing more efficient budget-allocation polices.